A Systematic Approach to Effective Conflict Management for Program. (January 2020) - Wang, Nannan; Wu, Guobin
Due to the complex structure and stakeholder relationships within a program, the management of conflicts in program therein proves more challenging than with a single project. The internal conflict of a program affects the performance of the program team and the success of the program. The previous researches focus more on the project level rather than program level, and lack a systematic analysis of management mechanism of team conflict. This research contributes to the program conflict literature by investigating the unique nature and solutions of conflict within program team, taking a systematic and innovative view on the organizational structure of a complex construction program. The findings reveal unique program conflict and their causes and impacts, and suggest the principles and alternative resolution strategies for conflict in program. The different roles of stakeholders in program conflict are analyzed by social network method. A program conflict management model is developed for the effective management of program conflicts. The model provides a systematic view of the learning cycle of program conflict management, including conflict identification, resolution, feedback, and prevention, of which many patterns are found distinct from project conflict management. The research results can benefit practitioners and researchers in better understanding and minimizing program conflict.